Tuberculous spondylitis of the lumbosacral region - Long-term follow-up of patients treated by chemotherapy, transpedicular drainage, posterior instrumentation, and fusion - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Objective: Tuberculosis spondylitis of the lumbosacral region has rarely been documented in the literature. We present an 87-month follow-up study of 7 of 62 patients with tuberculous spondylitis of the lumbosacral region treated by chemotherapy, transpedicular drainage, posterior instrumentation, and fusion. The purpose was to prove the hypothesis that chemotherapy with transpedicular drainage and single-stage posterior instrumentation-fusion is enough for the prevention of lumbar kyphosis and sagittal offset in selected cases. Methods: There were four men and three women, with average age of 53 years. All patients underwent transpedicular debridement, posterior fusion, and instrumentation. We studied the following data for consideration in these patients: most involved vertebra, vertebral body loss, progress of kyphosis, and sagittal offset. Results: The fourth lumbar vertebra was the most commonly involved vertebral segment. The average preoperative kyphosis was 17.5 and decreased to 5.4 degrees postoperatively. Mean preoperative and postoperative sagittal offset was 0.34 mm and -5 mm, respectively. The average postoperative sagittal offset was increased from -5 to -2 mm at the third month and henceforth remained unchanged. There was no recurrent infection. Conclusion: We consider that transpedicular drainage, posterior instrumentation, and fission constitute a less demanding operative technique for lumbosacral tuberculous spondylitis for the prevention of lumbar kyphosis and sagittal offset in patients without neurologic deficit and major vertebral body loss. This is the only lumbosacral tuberculous spondylitis series in which the patients were operated on with single-stage posterior surgery and merits a brief report in the light of the larger series.
Keywords: lumbosacral; tuberculous spondylitis; Pott's disease; KYPHOSIS; CHILDREN